Feasibility Analysis of a Livestock Business (Case Study at a Village-Owned Enterprise) - Kadek Diviariesty; Ni Nengah Seri Ekayani (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the feasibility of a livestock business managed by a Village-Owned Enterprise (BUMDes) located in Denpasar City, Bali, as part of a village food security program. This study uses a quantitative descriptive approach with a focus on financial analysis. The data used consist of primary data obtained through interviews with BUMDes managers and livestock farmers, as well as secondary data in the form of documents on financial records and activity reports. Analysis techniques include calculating production costs, revenue, operating profit, and livestock population growth over several harvest periods. The results show that the livestock business provides positive profits in each harvest period with an increasing trend in livestock numbers and operating profits from year to year. Thus, the livestock business managed by BUMDes is declared financially feasible and has the potential to support food security and improve the village economy.